1999
DOI: 10.1073/pnas.96.7.4113
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of nicotinic acetylcholine receptors by strychnine

Abstract: Strychnine, a potent and selective antagonist at glycine receptors, was found to inhibit muscle (␣ 1 ␤ 1 ␥␦, ␣ 1 ␤ 1 ␥, and ␣ 1 ␤ 1 ␦) and neuronal (␣ 2 ␤ 2 and ␣ 2 ␤ 4 ) nicotinic acetylcholine receptors (AcChoRs) expressed in Xenopus oocytes. Strychnine alone (up to 500 M) did not elicit membrane currents in oocytes expressing AcChoRs, but, when applied before, concomitantly, or during superfusion of acetylcholine (AcCho), it rapidly and reversibly inhibited the current elicited by AcCho (AcCho-current). Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…We report also that strychnine does not change the desensitization or voltage-dependence of WT␣7 or mut1 receptors, but acts on them as a ''pure'' competitive blocker. Nonetheless, in some heteromeric neuronal nAcChoRs, the strychnine block is noncompetitive and voltage dependent (1). Thus, our findings taken together with previous data (1, 2, 4-7) suggest avenues for the design of novel therapeutic agents for neurodegenerative diseases such as Alzheimer's and Parkinson's, at which the ␣7 subunit appears to play a role in both disease genesis and progression (15).…”
Section: Discussionmentioning
confidence: 56%
“…We report also that strychnine does not change the desensitization or voltage-dependence of WT␣7 or mut1 receptors, but acts on them as a ''pure'' competitive blocker. Nonetheless, in some heteromeric neuronal nAcChoRs, the strychnine block is noncompetitive and voltage dependent (1). Thus, our findings taken together with previous data (1, 2, 4-7) suggest avenues for the design of novel therapeutic agents for neurodegenerative diseases such as Alzheimer's and Parkinson's, at which the ␣7 subunit appears to play a role in both disease genesis and progression (15).…”
Section: Discussionmentioning
confidence: 56%
“…On the other hand, the previous reports have shown that various agents such as serotonin, strychnine, Ca 2+ channel blockers, polyamines, steroids such as progesterone and hydrocortisone, ethanol, and metal ion like Zn 2+ , regulate muscle or neuronal nicotinic acetylcholine receptors expressed in Xenopus oocytes [28][29][30][31][32][33][34][35]. Interestingly, the mechanism (i.e., voltage dependence or competition with acetylcholine for binding site) by which these substances regulate nicotinic acetylcholine receptors depend on the receptor subunit composition.…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish embryos were dechorionated and anesthetized in 0.02% tricaine dissolved in Evans solution and dissected according to previously described procedures (Drapeau et al, 1999). Briefly, spinal neurons in somites 5-15 were selected for recording based on their soma size and position as visualized by oblique illumination (Olympus BX61W1).…”
Section: Methodsmentioning
confidence: 99%
“…Embryos were anesthetized in 0.02% Tricaine and immobilized in 0.75% low-melting point agarose. A total of 3 mM CNQX, 5 mM APV, 1 M TTX, or saline was coinjected with 0.1% Fast Green dye and 2% FITC cell-permeant fluorescent tracer dye, in Evans medium (134 mM NaCl, 2.9 mM KCl, 2.1 mM CaCl 2 , 1.2 mM MgCl 2 , 10 mM glucose, 10 mM HEPES, pH 7.8, with NaOH) (Drapeau et al, 1999). Glass needles were pulled and mounted on a pipette holder, and 65 ms injections at 40 psi were delivered using a Picospritzer III (Parker Hannifin).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation